Pengaruh Perlakuan Media Tanam dan Ekoenzim terhadap Produksi Tanaman Bawang Merah - Luta, Devi Andriani; Siregar, Maimunah; Syam, Fariz Harindra (Agrosains : Jurnal Penelitian Agronomi, 2022)
Improving the productivity of shallots through the continuous application of inorganic fertilizers can result in decreased land productivity; one way to overcome further impacts that will arise from such use is through the provision of organic matter. The aim of this study was to determine the effect of planting media and ecoenzyme treatment on shallot production. This study used a factorial randomized block design which consisted of 2 treatment factors, namely first factor was Planting Media (M) consisting of M0: 100% topsoil, M1: topsoil (75%) + chicken manure compost (25%), M2: topsoil (50%) + chicken manure compost (50% and M3: topsoil (25%) + chicken manure compost (75%). The second factor was Ecoenzyme (E) which consists of 0, 10, 20 and 30ml. Plant observations included wet tuber weight per plot (g), dry bulb weight per plot (g) and tuber diameter (mm). Data analysis method was analysis of variance and further test for real treatment using Duncan’s multiple Range Test. The results obtained that the provision of planting media in the form of 75% topsoil + 25% compost was able to respond to the production of shallots. Ecoenzyme and the interaction between ecoenzyme in the growing media gave an insignificant effect on the production of shallots as wet tuber weight per plot, dry bulb weight per plot and tuber diameter.